Gugatan Citizen Law Suit: Progresivitas Penyelesaian Sengketa Lingkungan Hidup dalam Praktik Hukum di Indonesia - Gracia Gracia; Mella Ismelina Farma Rahayu (Syntax Literate, 2023)
The legal progressivity of environmental law looks at the development of the world and humans so that the law moves for the benefit of humans and ecological principles. The effectiveness of environmental law is inseparable from the performance of administrative and law enforcement officials related to citizen law suit. Some court decisions have rejected citizen law suits due to problems in setting the formal requirements of the lawsuit. The aim of this research is to determine the mechanism and progressivity of citizen law suit lawsuits as an effort to enforce environmental law in Indonesia. This research uses normative juridical research that focuses on statutory approach and conceptual approach. The search results are based on secondary data collection consisting of primary, secondary, and tertiary legal materials through literature studies. While the data analysis method uses a qualitative research method that emphasizes analysis or descriptive and is concluded using the deductive method. The results showed that the citizen law suit was aimed at the government with the argument of tort in Article 1365 of the Civil Code, the government was considered to have failed in carrying out its obligations to protect and manage the environment. Citizen law suit as a form of environmental law progressivity that refers to civil procedural law in Indonesia, the difference lies in the formal requirements based on KMA Number 36/KMA/SK/II/2013. Therefore, progressive law and law enforcement in Indonesia must be considered again for the realization of human welfare and natural balance, especially the regulation of citizen law suits.